Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006274.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Medically assisted nutrition for palliative care in adult patients

Abstract: Background Many palliative care patients have a reduced oral intake during their illness. The management of this can include the provision of medically assisted nutrition with the aim of prolonging the length of life of a patient, improving their quality of life, or both. Objectives To determine the effect of medically assisted nutrition on the quality and length of life of palliative care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…In our study, 24% percent of patients who received the dedicated encounter did not wish to rely on artificial nutrition. This preference is important to identify, especially among patients with advanced comorbidity and at high risk of cognitive decline, as there is no evidence to suggest that artificial nutrition prolongs survival, or improves quality of life in such patients (27, 28). The preference to avoid artificial nutrition is consistent with a previous cross sectional study where 39% of patients surveyed upon hospitalization for symptoms of advanced cancer expressed preference to forgo artificial nutrition (29).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 24% percent of patients who received the dedicated encounter did not wish to rely on artificial nutrition. This preference is important to identify, especially among patients with advanced comorbidity and at high risk of cognitive decline, as there is no evidence to suggest that artificial nutrition prolongs survival, or improves quality of life in such patients (27, 28). The preference to avoid artificial nutrition is consistent with a previous cross sectional study where 39% of patients surveyed upon hospitalization for symptoms of advanced cancer expressed preference to forgo artificial nutrition (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because clinically relevant methods to distinguish impaired nutritional status caused by cachexia from that caused by simple starvation and secondary symptoms are not well developed [3,7]. A Cochrane review from 2009 [14] concluded that there are insufficient good quality studies to make any recommendations for practice with regards to the use of ETF or PN in palliative care patients. Raijmakers et al ’s more recent review [15] on cancer patients in the last week of life supports this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…There is insufficient evidence that EN can improve patient outcomes and has been associated with increased burden and discomfort. 52,54 Although there may be times where EN may provide some value for personal, cultural or religious reasons, in general, at EoL, EN does not align with CKD-RSC goals of maintaining dignity and comfort, relieving symptom burden and improving QoL. 50…”
Section: Is Enteral Nutrition Appropriate At Eol?mentioning
confidence: 99%